Glucose but not KCl diminishes submembrane granule turnover in mouse beta-cells. (October 2017) - Brüning, Dennis; Reckers, Kirstin; Drain, Peter; Rustenbeck, Ingo
Abstract : KCl depolarization is widely used to mimic the depolarization during glucose-stimulated insulin secretion. Consequently, the insulin secretion elicited by KCl is often regarded as the equivalent of the first phase of glucose-induced insulin secretion. Here, the effects of both stimuli were compared by measuring the secretion of perifused mouse islets, the cytosolic Ca 2+ concentration of single beta-cells and the mobility of submembrane insulin granules by TIRF microscopy of primary mouse beta-cells. Two cargo-directed granule labels were used namely insulin-EGFP and C-peptide-emGFP. The granule behaviour common to both was used to compare the effect of sequential stimulation with 40 mM KCl and 30 mM glucose and sequential stimulation with the same stimuli in reversed order. At the level of the cell secretory response, the sequential pulse protocol showed marked differences depending on the order of the two stimuli. KCl produced higher maximal secretion rates and diminished the response to the subsequent glucose stimulus, whereas glucose enhanced the response to the subsequent KCl stimulus. At the level of granule behaviour, a difference developed during the first stimulation phase in that the total number of granules, the short-term resident granules and the arriving granules, which are all parameters of granule turnover, were significantly smaller for glucose than for KCl. These differences at both the level of the cell secretory response and granule behaviour in the submembrane space are incompatible with identical initial response mechanisms to KCl and glucose stimulation.